NETWORK APPLICATION IN OIL PALM SEEDLING WATERING MONITORING SYSTEM USING ESP32 - Anang Arif Hibaturrahman; Noveri Lysbetti Marpaung; Sakti Hutabarat; Edy Ervianto; Yogie Rinaldy Ginting; Nurhalim; Rahyul Amri (SOSIOEDUKASI, 2026)
This research aims to design and implement an Internet of Things (IoT) based monitoring and control system for watering and fertilizing oil palm seedlings using the ESP32 microcontroller. The system was developed to overcome the weaknesses of manual watering methods which still rely on estimated soil conditions so that they are less efficient and risk inhibiting seedling growth. The system utilizes a soil moisture sensor to detect soil moisture and a DHT22 sensor to monitor temperature and air humidity in real-time. The data from the sensor readings is sent through the internet network and displayed on the Telegram application as a medium for remote monitoring and control. The system was tested for 14 days under morning and evening watering conditions with Quality of Service (QoS) analysis using throughput, delay, packet loss, and jitter parameters. The results of the study show that the system successfully works automatically and is able to monitor the environmental conditions of the seedlings in real-time. The average value of the QoS index in morning watering was 2.46 with a quality percentage of 61.50%, while afternoon watering was 2.39 with a quality percentage of 59.75%, both of which are in the medium category. The packet loss parameter shows excellent performance with packet loss close to zero, while delay and jitter are in the good to good category. However, the throughput parameters are still relatively low, so it is necessary to improve network quality for system optimization. Overall, the system is designed to support the monitoring and control process of watering oil palm seedlings automatically with a fairly stable data communication quality.